Psikologi Pendidikan di dalam al-Qur’an - Rohimah, Siti; Haerullah, Haerullah; Adin, Ahmad Muchlis; Rozzaq, Abdur (TSAQOFAH, 2024)
Educational psychology is an important foundation in curriculum development and understanding student character. The Qur'an plays a central role in the perspective of Islamic education, emphasizing the concepts of extraordinary life. Islamic psychology enriches the view of psychology with religious values. Human beings in the Islamic view have unique potentials and special traits, such as learning abilities and good and bad tendencies. The Qur'an encourages people to make use of reason and go through the learning process, paying attention to the ethics of students towards teachers. The verses of the Qur'an reveal the motivation for learning through requests, commands, exhortations, and threats. It includes intrinsic drives such as curiosity and learning tendencies as well as extrinsic drives such as rewards and commands. The harmony between material and spiritual aspects is important in overcoming internal conflicts, while the positive human potential is often emphasized in the hope for change for the better. The Qur'an also describes man's psychological struggle between conflicting traits such as lust and spiritual instinct. By combining psychological views and religious teachings, this approach provides a rich foundation for human self-understanding and development in the context of education and life.